2022
DOI: 10.3389/fphys.2022.882550
|View full text |Cite
|
Sign up to set email alerts
|

Lens Aquaporins in Health and Disease: Location is Everything!

Abstract: Cataract and presbyopia are the leading cause of vision loss and impaired vision, respectively, worldwide. Changes in lens biochemistry and physiology with age are responsible for vision impairment, yet the specific molecular changes that underpin such changes are not entirely understood. In order to preserve transparency over decades of life, the lens establishes and maintains a microcirculation system (MCS) that, through spatially localized ion pumps, induces circulation of water and nutrients into (influx) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 138 publications
(249 reference statements)
0
3
0
Order By: Relevance
“…Previous publications have thoroughly reviewed the importance of AQPs in the lens MCS ( 12 , 21 , 56 , 57 , 58 , 59 ). Briefly, AQPs serve as water channels that facilitate water permeability in fiber cells ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have thoroughly reviewed the importance of AQPs in the lens MCS ( 12 , 21 , 56 , 57 , 58 , 59 ). Briefly, AQPs serve as water channels that facilitate water permeability in fiber cells ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have thoroughly reviewed the importance of aquaporins in the lens MCS (12, 27, 7578). Briefly, aquaporins serve as water channels that facilitate water permeability in fiber cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that both wild-type and mutant PCS2+MIP lens fibres were uniformly transparent (Figure 12). DISCUSSION Aquaporins (AQPs) mainly mediate passive free water transfer across biofilms along the osmotic pressure gradient, thereby they play an important role in regulating lens water metabolism, maintaining lens internal microcirculation homeostasis, and participating in lens physiological functions and transparency [40][41] . AQPs are a superfamily of MIPs of approximately 30 kDa that are expressed in prokaryotes and eukaryotes, three of which are present in the mammalian lens (AQP0, AQP1, and AQP5) [42] .…”
Section: Novel Mip Gene Mutation Causes Congenital Cataractmentioning
confidence: 99%